Real-world outcomes of immune checkpoint inhibitor-based combination therapy in older adult patients with metastatic renal cell carcinoma: a multi-center, retrospective analysis - Ikoma, Hiroaki; Hamamoto, Shuzo; Tasaki, Yoshihiko; Tomita, Misato; Sakata, Takuya; Suzuki, Hiroko; Noda, Yusuke; Usami, Masayuki; Tsubouchi, Yohei; Mimura, Yoshihisa; Morikawa, Toshiharu; Nagai, Takashi; et al. (Frontiers in Immunology, 2025)
IntroductionImmune checkpoint inhibitor (ICI)-based combination therapy has revolutionized first-line treatment outcomes for metastatic renal cell carcinoma (mRCC). In this study, we aimed to retrospectively analyze real-world clinical outcomes and toxicities of first-line ICI-based combination therapies, specifically nivolumab plus ipilimumab (IO+IO) and ICIs plus tyrosine kinase inhibitors (IO+TKI), in Japanese patients with mRCC aged ≥ 75 years compared with non-older adult patients.MethodsWe retrospectively enrolled 156 patients with mRCC who received first-line IO+IO or IO+TKI between September 2018 and June 2024 at eight Japanese institutions. Patients were categorized into an older adult group (≥ 75 years, n=49) and a non-older adult group (< 75 years, n=107). We evaluated objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and adverse events (AEs).ResultsThe overall ORR (47% vs. 59%, p=0.43) and DCR (86% vs. 83%, p=0.65) were comparable between groups. No significant differences were observed in PFS (median: 15.5 vs. 17.0 months, p=0.78) or OS (NA vs. 52.2 months, p=0.61). In the IO+IO regimen, the ORR, DCR, PFS, OS, and AE rates were comparable across age groups. However, in the IO+TKI 〇 regimen 　×cohort, the ORR was significantly lower in older adults (55% vs. 81%, p=0.04), and treatment discontinuation due to AEs was significantly higher in older adults (60% vs. 32%, p=0.02), with a shorter time to discontinuation despite no difference in the initial TKI dose and RDI. The non-older adult group showed significantly better PFS with IO+TKI compared with IO+IO (hazard ratio: 2.37, p=0.02). In contrast, in the older adult group, PFS and OS were approximately equivalent between the two regimens.ConclusionOur real-world data indicated that ICI-based combination therapies are effective in patients with mRCC aged ≥75 years, with outcomes largely non-inferior to non-older adult patients. However, the comparable efficacy of IO+TKI and IO+IO in the older adult group, which may differs from that in the non-older adult group, highlights the importance of understanding the distinct characteristics of each regimen for individualized treatment selection and careful management, particularly regarding AE monitoring and dose adjustment in older adult patients receiving IO+TKI.